Conceptualization Of Community-Based Tourism In Kampung 99 - Aninda, Maria Paskalia; Yudi Bachrioktora (Forum Ilmu Sosial, 2024)
Kampung 99 Pepohonan is a tourist destination located in the Limo area, Depok City, which one family founded to develop into a village community; this tourist destination attracts visitors through a variety of environmentally friendly and green tourism-oriented tourism activities in the middle of urban areas. The central vision of Kampung 99 Pepohonan management is a strong desire to apply the concept of healthy living by creating a healthy environment so that healthy behavior arises. This research refers to the idea of community-based tourism (CBT), which is a type of tourism where residents run activities for their welfare and the application of social capital as the basis for the construction of meaning, trust, togetherness, tolerance, and participation which are closely related to community survival strategies. This research aims to identify social capital within the scope of the Kampung 99 community with local communities through basic principles in community-based tourism. This type of research is ethnography with a qualitative descriptive approach, while data collection is done through observation, interviews, and literature studies. This research shows that the Kampung 99 community has successfully empowered the environment through excellent and efficient utilization and management. The Kampung 99 community is oriented towards the common principles of life through a vision and mission with cooperation to achieve community goals and welfare.